Forensic Auditing in Fraud Detection and Prevention: Integration of Technology, Internal Audit, and Anti-Fraud Regulation - Mohammad Kholis Fajrun Najih (Fairness, 2025)
Objective: This study aims to analyze fraud trends and patterns in the banking and corporate sectors, evaluate the effectiveness of internal audits in detecting fraud, and examine the role of technology and regulation in improving audit fraud detection.Research Design & Methods: This research uses a systematic literature review (SLR) method with a qualitative descriptive approach. Data was collected from the Scopus database using the Publish or Perish tool, resulting in 93 articles related to forensic audit, auditing, and fraud detection. The articles obtained were then filtered down to the 20 most relevant ones and analyzed in four main aspects.Findings: The findings suggest that fraud in the banking and corporate sectors is becoming increasingly complex, involving financial statement manipulation, money laundering, and the use of advanced technology. Internal audits with forensic auditing have proven more effective in detecting fraud, especially with the involvement of specialists and technologies such as AI, big data, and blockchain. Anti-fraud regulations play a crucial role; however, their implementation still faces challenges, including policy harmonization and limited forensic auditor resources.Implications & Recommendations: This research emphasizes the importance of strengthening internal control systems, using advanced technology in audits, and increasing the capacity of forensic auditors to increase audit effectiveness in detecting and preventing fraud.Contribution & Value Added: This research makes an academic contribution by identifying the latest trends in fraud detection and evaluating the effectiveness of forensic auditing in facing modern challenges.